2021
DOI: 10.1101/2021.01.23.21250197
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Opportunistic Assessment of Ischemic Heart Disease Risk Using Abdominopelvic Computed Tomography and Medical Record Data: a Multimodal Explainable Artificial Intelligence Approach

Abstract: Current risk scores for predicting ischemic heart disease (IHD) risk—the leading cause of global mortality—have limited efficacy. While body composition (BC) imaging biomarkers derived from abdominopelvic computed tomography (CT) correlate with IHD risk, they are impractical to measure manually. Here, in a retrospective cohort of 8,197 contrast-enhanced abdominopelvic CT examinations undergoing up to 5 years of follow-up, we developed improved multimodal opportunistic risk assessment models for IHD by automati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…However, the performance of these scores, measured by the area under the receiver operating characteristic curve (AUC), has been modest when testing them in more diverse patient populations. Thus, Chaves et al developed a framework to use deep learning and machine learning models that enable opportunistic risk assessment for ischemic heart disease (IHD) using automatically measured imaging features from abdominopelvic CT examinations in combination with information from the patient's EMR ( 15 ).…”
Section: Multimodal Data Fusion Across Different Use Casesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the performance of these scores, measured by the area under the receiver operating characteristic curve (AUC), has been modest when testing them in more diverse patient populations. Thus, Chaves et al developed a framework to use deep learning and machine learning models that enable opportunistic risk assessment for ischemic heart disease (IHD) using automatically measured imaging features from abdominopelvic CT examinations in combination with information from the patient's EMR ( 15 ).…”
Section: Multimodal Data Fusion Across Different Use Casesmentioning
confidence: 99%
“… Architecture of multi-modal data fusion combining Imaging and clinical data. Figure taken from Chaves et al ( 15 ). In their described framework, readily available CT images are combined with clinical data (e.g.…”
Section: Multimodal Data Fusion Across Different Use Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…These models, while innovative, fall short of fusing imaging data directly with clinical information. Chaves et al 38 fused L3 slices from CT for body composition analysis, and known clinical risk factors through late fusion, for opportunistic screening for ischemic heart disease. They observed that fusion modeling outperforms single-modality models in terms of screening performance.…”
Section: Multimodality Data Fusionmentioning
confidence: 99%
“…In this work we focus on risk scoring from abdominal CT scans, which has only been studied previously in a handful of works. 9, 27, 28 Abdominal CT are rich with biomarkers known to be relevant to cardiovascular risk such as visceral fat and aortic plaque. 29, 30 This is the first work to feed the entire abdominal CT scan into a deep learning model.…”
Section: Purposementioning
confidence: 99%